Highlights of the ESC 2014 Conference - Edward Mullins (The University of Alabama, 2022)
Coverage of the 2014 Annual Conference of the Engagement Scholarship Consortium, featuring The keynote address from Dr. Rajesh Tandon Poster Session Award Winners First Place-Integrating High-Impact Scholarship into a General Education Class. By Careen Yarnal and Hsin-Yu Chen (The Pennsylvania State University) Second Place-The Impact of Homelessness and Incarceration on the Health of Women. By Louanne Keenan and Rabia Ahmed (University of Alberta) Third Place-Does Service-Learning Make Graduates (Feel) More Employable? By Paul H. Matthews and Jeffrey H. Dorfman (University of Georgia) Honorable Mention with Distinction Illustrating the Impacts: Global Community Engaged Design. By Rebekah Radtke and Travis Hicks (University of North Carolina-Greensboro). Oklahoma Cooperative Extension Service: Building an Interculturally Competent Community. By Maria G. Fabregas Janeiro and Jorge Atiles (Oklahoma State University). Characteristics of Effective Practice by Faculty in Service-Learning Courses. By Paul H. Matthews (University of Georgia) and Andrew J. Pearl (University of North Georgia).